Analisis Implementasi Pemungutan Pajak Bumi dan Bangunan Bagi Pendapatan Otonomi Daerah di Indonesia - Abdullah Mubarak Lubis; Radiansyah Radiansyah; Maycika Anggreini (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research explains that land and building tax (PBB) is a crucial fiscal instrument in the global taxation system, with the aim of supporting government spending on public services, regulating land use, and potentially as a redistribution tool. This article addresses the fundamental ideas, goals, and effects of PBB in Indonesia, highlighting its important role in financing national development. The discussion involves aspects of billing, the basis of collection, the collection system, payment procedures, as well as the taxpayer's right to object and appeal. Emphasis is given to key principles, such as openness, fairness, legal certainty, and public participation in the implementation of PBB. Although PBB contributes significantly to economic development, the article also identifies several critical issues, including property value assessment, social inequality, and economic effects that must be taken into account while managing a just and effective tax system. This article offers a thorough analysis of the PBB as a tool for policy that is essential to the welfare of society and the growth of the nation.